The ability of branched-chain amino acid-to-tyrosine ratio (BTR) to assess preoperative liver function of patients with hepatocellular carcinoma - Akihiko Takagi; Akitsugu Fujita; Satoshi Tokuda; Shunsuke Tamura; Eiji Nakatani; Hideyuki Kanemoto; Noriyuki Oba (PLoS ONE, 2026)
Assessment of hepatic functional reserve is critically important for preventing serious complications after hepatectomy such as liver failure. While the indocyanine green clearance test (ICG) is a liver-specific test that is not affected by other organs and is commonly used to evaluate liver reserve capacity. We lack knowledge regarding what test should be performed for patients with jaundice, portal shunts, or intolerance whose liver function cannot be accurately assessed by ICG. To close this gap, we focused on changes in amino acid metabolism associated with impaired liver function. The branched-chain amino acid-to-tyrosine ratio (BTR) reflects the severity of liver disease. The research objectives are to evaluate whether BTR is useful as an alternative test to ICG. The primary endpoint of this study is to clarify the correlation between BTR and ICG. The secondary endpoints are to provide pathological confirmation of liver fibrosis and clarify the relationship with short- and long-term outcome and to examine whether it is clinically significant as a marker of preoperative liver reserve capacity. This retrospective single-center cohort study included patients who underwent hepatectomy for HCC between January 2011 and December 2016. In this study, 235 patients were enrolled, with a median BTR of 5.58. The BTR and indocyanine green stagnation rates at 15 min (ICG-R15) showed a significant correlation (r = −0.57, p < 0.001), whereas 1/BTR showed an even stronger correlation (r = 0.66, p < 0.0001). Conversion formulas that is a regression equation predicting ICG test results with BTR as an explanatory variable were analyzed. In addition to its correlation with ICG-R15, BTR was significantly associated with liver fibrosis in the background liver pathology of resected specimens, demonstrating higher sensitivity for detecting cirrhosis compared to ICG. The high BTR group exhibited significantly longer survival than the low BTR group (p = 0.020). The results indicate that BTR and ICG are significantly correlated. Comparable to ICG, BTR is a predictor of liver fibrosis and a prognostic factor for postoperative outcomes in patients with HCC. Although 99mTc-GSA scintigraphy has been reported to correlate with IGC, the correlation coefficient and number of cases in this study are equivalent. BTR can be tested through routine blood sampling. The results of this study demonstrate the potential for clinically evaluating preoperative hepatic reserve capacity in a less invasive, more cost-effective without facility limitations.